E-Commerce Distribution Efficiency Analysis To Enhance Culinary Msmes’ Performance In Jabodetabek - Indarsari, Aisyah (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to describe the level of efficiency of the distribution of culinary MSME products through e-commerce platforms in the Greater Jakarta area based on cost, time, service, and output indicators. The research method used was quantitative descriptive with a questionnaire instrument on a Likert scale of 1–5, which was compiled based on the SCOR model, logistics distribution theory, and Logistics Service Quality (LSQ) and SERVQUAL dimensions. A total of 30 culinary MSMEs who actively use e-commerce services such as GoFood, GrabFood, and ShopeeFood became research respondents. The results showed that the distribution costs were relatively high (average 3.16), mainly due to platform commissions and packaging costs. The distribution time dimension is in the good category (3.74), although in practice there is still a potential for delay due to the process of picking up products by drivers. Service/reliability earned a high score (3.87), indicating customer satisfaction with order accuracy, product condition, and tracking. The output of the effort showed an increase (3.84) in sales, reach, and customer satisfaction. An efficiency index of 1.12 indicates that distribution through e-commerce platforms as a whole is relatively efficient because the output produced is higher than the cost and time inputs. These findings confirm that the use of e-commerce platforms plays an important role in supporting the efficiency of the distribution of culinary MSMEs in urban areas. However, optimizing cost strategies and platform selection is still needed so that MSMEs can achieve a more sustainable level of efficiency.